Microwave dielectric properties of Ca[(Li1/3Nb2/3)(1-x) Ti-x]O3-delta ceramics with glass - Ha, Jong-Yoon; Choi, Ji-Won; Kang, Chong-Yun; Yoon, Seok-Jin; Choi, Doo Jin; Kim, Hyun-Jai (SPRINGER, 2006)
The effect of the addition of glass on the densification, low temperature sintering, and microwave dielectric properties of the Ca[(Li1/3Nb2/3)(1-x) Ti-x]O3-delta(CLNT) was investigated. Addition of glass (B2O3-ZnO-SiO2-PbO system) improved the densification and reduced the sintering temperature from 1150 degrees C to 900 degrees C of Ca[(Li1/3Nb2/3)(1-x) -Ti-x]O3-delta microwave dielectric ceramics. As increasing glass contents from 10 wt% to 15 wt%, the dielectric constants (epsilon(r)) and bulk density were increased. The quality factor (Q-f(0)), however, was decreased slightly. The temperature coefficients of the resonant frequency (tau(f)) shifted positive value as increasing glass contents over Ti content is 0.2 mol. The dielectric properties of Ca[(Li1/3Nb2/3)(0.75)Ti-0.25]O3- with 10 wt% glass sintered at 900 degrees C for 3 h were epsilon(r) = 40 Q center dot f(0) = 11500 GHz, tau(f) = 8, ppm/degrees C. The relationship between the microstructure and dielectric properties of ceramics was studied by X-ray diffraction (XRD), and scanning electron microscope (SEM).
Keywords: RESONATOR; TI